Liver visfatin expression in morbidly obese patients with nonalcoholic fatty liver disease undergoing bariatric surgery - Kukla, Michał; Ciupińska-Kajor, Monika; Kajor, Maciej; Wyleżoł, Mariusz; Żwirska-Korczala, Krystyna; Hartleb, Marek; Berdowska, Agnieszka; Mazur, Włodzimierz (Polish Journal of Pathology, 2010)
Background : Visfatin has been identified as a new adipokine with proinflammatory and immunomodulating properties. It seems to interfere with immune and fibrogenic process in nonalcoholic fatty liver disease (NAFLD). The aim was to assess visfatin expression in the liver tissue and its association with biochemical parameters and morphological features in NAFLD patients. Material and methods : The study included 40 severely obese patients with NAFLD who underwent intraoperative wedge liver biopsy during a bariatric operation. Immunohistochemical assay was carried out with the use of a visfatin mice monoclonal antibody. Results : Visfatin expression in the liver was observed in all patients. The expression was significantly higher in patients with fibrosis (p = 0.036) and was positively correlated with the fibrosis stage (r = 0.52, p = 0.03). There was no difference between patient with nonalcoholic steatohepatitis (NASH) and simple steatosis (p = 0.54). Inflammatory activity and NAS (NAFLD Activity Score) score were not associated with visfatin expression. There was a tendency of more evident visfatin liver expression in morbidly obese patients with diabetes mellitus. Conclusion : Our study showed a positive association between visfatin and the fibrosis stage in NAFLD. This observation suggests a potential role of this adipokine in the pathogenesis and progression of NAFLD. Visfatin expression does not seem to be associated with liver steatosis and inflammation.